Transformasi Produk Tekstil Melalui Implementasi dan Efektivitas Pembuatan Batik Ecoprint Daun Tumbuhan Khas Pacitan Sebagai Wujud Pelestarian dan Eco-branding Batik - Fitriyati, Umi; Setiawan, Deny; Rakhmawati, Yunita; Anggraini, Dinar Arsy; Firdaus, Zahra; Hayuana, Wachidah (JPM PAMBUDI, 2024)
The batik industry in Pacitan well known for its unique motifs of pace plants. The batik production process was carried out at least three times, so that the volume of disposal of batik wax waste into the environment becomes greater. Ecoprint training is an activity carried out with the aim of facilitating the community in the context of training in making Ecoprint batik and utilizing digital media to create ecobranding batik. The method in this activity used the ABCD (Asset-based Community Development) method starting with pre-implementation, execution, implementation, and results. The first meeting provided ecoprint training by providing an understanding of all ecoprint making activities from exploring materials, laying leaves to form motifs, explaining pounding and steam techniques, fixation, and drying. The second meeting provided digital branding training by providing understanding and practice related to creating digital product branding. The results of this activity are Ecoprint batik and the creation of logos and product content on social media. This activity shows positive impacts including preserving nature and culture, increasing income, and increasing environmental awareness.